Amplification and pyrosequencing of near-full-length hepatitis C virus for typing and monitoring antiviral resistant strains. (May 2016) - Trémeaux, P.; Caporossi, A.; Ramière, C.; Santoni, E.; Tarbouriech, N.; Thélu, M.-A.; Fusillier, K.; Geneletti, L.; François, O.; Leroy, V.; Burmeister, W.P.; André, P.; et al.
Abstract: Directly acting antiviral drugs have contributed considerable progress to hepatitis C virus (HCV) treatment, but they show variable activity depending on virus genotypes and subtypes. Therefore, accurate genotyping including recombinant form detection is still of major importance, as is the detection of resistance-associated mutations in case of therapeutic failure. To meet these goals, an approach to amplify the HCV near-complete genome with a single long-range PCR and sequence it with Roche GS Junior was developed. After optimization, the overall amplification success rate was 73% for usual genotypes (i.e. HCV 1a, 1b, 3a and 4a, 16/22) and 45% for recombinant forms RF_2k/1b (5/11). After pyrosequencing and subsequent de novo assembly, a near-full-length genomic consensus sequence was obtained for 19 of 21 samples. The genotype and subtype were confirmed by phylogenetic analysis for every sample, including the suspected recombinant forms. Resistance-associated mutations were detected in seven of 13 samples at baseline, in the NS3 ( n  = 3) or NS5A ( n  = 4) region. Of these samples, the treatment of one patient included daclatasvir, and that patient experienced a relapse. Virus sequences from pre- and posttreatment samples of four patients who experienced relapse after sofosbuvir-based therapy were compared: the selected variants seem too far from the NS5B catalytic site to be held responsible. Although tested on a limited set of samples and with technical improvements still necessary, this assay has proven to be successful for both genotyping and resistance-associated variant detection on several HCV types.